The Role of Meta-cognition in Students' Addiction Potential Tendency - Hajloo, Nader (Kowsar, 2014)
BACKGROUND: Addiction for narcotics is a dangerous reality, especially in teenagers and young persons, and is one of the most important socioeconomic and health problems, threatens the human society and leads to social stagnancy in various aspects. OBJECTIVES: The present study aimed at determining Meta-cognitive relationship with addiction potential tendency in students and determining the distribution of each Meta-cognitive dimension in predicting addiction potential tendency. MATERIALS AND METHODS: The descriptive-correlative method was used for conducting this research. The research target population included all students of Ardebil Mohaghegh University. A sample of 380 subjects was selected randomly from this demographic population by cluster multistage sampling. We used Weed and colleagues’ questionnaire of addiction to assess addiction potential tendency, and the Meta-cognitive scale of Wells and colleagues for evaluating Meta-cognition. Data gathered were analyzed by multifold Regression via simultaneous entrance method. RESULTS: The rate of students’ addiction potential tendency can be predicted by having characteristics of their Meta-cognition. It also appeared that among the five parameters of Meta-cognition, the role of three parameters required for controlling thoughts, uncontrollability and risk, and positive beliefs about anxiety were of great importance in predicting addiction potential tendency in students. CONCLUSIONS: The results of this research have important implications regarding the attention of students’ counselors to Meta-cognitive dimensions in order to prevent students’ tendency for addiction.